Association between bronchial asthma in atopic children and their number of siblings - Johan El Hakim Siregar; Lily Irsa; Supriatmo Supriatmo; Sjabaroeddin Loebis; Rita Evalina (Indonesian Pediatric Society, 2014)
Background The prevalence of asthma in children has increased in many countries. Environmental factors are believed to play an important role and an inverse relationship between number of siblings and atopic disorders has been observed.Objective To assess for an association between bronchial asthma in atopic children and their number of siblings.Methods A cross-secrional study was conducted from June to November 2010 in three elementary schools in Medan, North Sumatera. Trace cards from the Allergy-Immunology Indonesian Pediatric Association (IDAI) Working Group and questionnaires on the clinical history of atopy were used to screen children with the risk of atopy. The International Study of .Asthma and Allergies in Childhood (ISAAC) questionnaire to screen for bronchial asthma was distributed to children aged 7-10 years with a history of asthma, allergic rhinitis or atopic dermatitis. Subjects were divided into two groups, those with <3 siblings and those with 2:3 siblings. Chi-square test was used to analyze differences in bronchial asthma prevalence between the two groups.Results Ninety-six subjects enrolled in the study, with 48 subjects per group. The prevalence of bronchial asthma was significantly higher in atopic children who had <3 siblings than in children with 2:3 siblings (73.5% and 26.5%, respectively; P=0.04).Conclusion Bronchial asthma was significantly more frequent in children with less than 3 siblings compared to those with 3 or more siblings.